Straw biochar hastens organic matter degradation and produces nutrient-rich compost. (January 2016) - Zhang, Jining; Chen, Guifa; Sun, Huifeng; Zhou, Sheng; Zou, Guoyan
Highlights: Straw biochar improved water-soluble nutrient ions contents during composting. Straw biochar enhanced the degradation of organic matter and maturity. The product with biochar addition became mature after composting for 42 days. A final concentration of 10–15% straw biochar was optimal. Abstract: Biochar derived from wheat straw was added to pig manure in amounts equivalent to 5%, 10%, or 15% (w/w, wet weight). The ratios of NH4 + /NO3 − and of UV light absorption at a wavelength of 254 nm (SUV254 ) and dissolved organic carbon (DOC) indicated that compost with 10–15% biochar became more mature and more humified within 42 days of composting, and the content of DOC and the concentration of NH4 + in such compost decreased by 37.5–62.0% and 4.0–20.9%, respectively, compared to the corresponding levels in the control. Addition of biochar lowered the pH and increased electrical conductivity by 7.0–37.5% compared to the control and also increased the concentrations of water-soluble nutrients including PO4 3− (5.6–7.4%), K + (14.2–58.6%), and Ca 2+ (0–12.5%). It is therefore recommended that straw biochar be added to pig manure at 10–15% by weight.